A boy named Ibrahim - Sarte, Sitti Aminah (Adarna House, Inc., 2014)
"Young Ibrahim knows that as a Muslim, it is his duty to observe his five daily prayers. Take a peek into a Muslim child's life and see how Ibrahim performs these prayers throughout the day, and why praying is important to him."